Rural livelihood diversification and income inequality in Akinyele Local Government area, Ibadan, Oyo State, Nigeria (2014)
The pattern of income distribution has been a major concern in the developing world. This is because high levels of income inequality are likely to create a hostile atmosphere for economic growth and development. This study examined rural livelihood strategies and their contribution to the overall income inequality of households in Akinyele local government area of Oyo state. Primary data employed in the study were obtained from 105 respondents selected through a multi-stage sampling technique. Data were analyzed using descriptive statistics, multinomial logit and the generalized entropy inequality indices as a measure of inequality. The distribution of respondents by type of livelihood strategy adopted revealed that almost half of the respondents adopted the combination of farm and non-farm strategy while 14.3% and 40.0% adopted only farm and non-farm strategy respectively. Income inequality was the highest among non-farming households and the lowest among farming households, implying that income from non-farm activities contributed most to income inequality in the study area. The study revealed that the major factor which negatively influenced the choice of farming as a livelihood strategy was household size while factors such as age and land ownership had positive and negative effects on the adoption of the non-farm strategy respectively. The study recommends that policies targeted at rural dwellers should centre on improved access to productive assets such as land for the landless farmers as well as the provision of improved technology, which could encourage the ageing farming population to engage in farming activities.